Protease and Amylase Activities of Javaen barb (Systomus rubripinnis Val.) - Untung Susilo; Farida Nur Rachmawati; Eko Setio Wibowo (Jurnal Biodjati, 2022)
Studies on morphology, growth, and reproduction have been carried out on wild Javaen barb, but there was no information on its digestive capacity; therefore, the research was conducted to determine protease and amylase activities in the digestive tract. This study used a total of 50 barbs with body weights between 13.56 -128.93g / fish. The measurement of enzyme activity was carried out using the spectrophotometer method. The results showed that differences in fish size resulted in differences in protease activity, but not for amylase. Fish with a small size have a higher protease activity than fish with a larger size. The protease activity did not differ between pH 6.9 to 10.0 but was higher than pH 12.5. Protease activity also did not vary between the anterior and posterior intestine and between 30-50°C. Amylase activity also found no difference between the anterior and posterior intestine, but there was a difference in activity between temperatures of 30-50°C. In conclusion, protease activity occurs in a neutral to alkaline environment, and there were differences in protease activity between different body sizes but not between intestinal segments. Amylase activity occurs throughout the intestine and decreases at temperatures of 50°C.